Hak Asasi Manusia Kaitannya dengan Struktur Sosial Masyarakat - Habib Adji (Universitas Islam Indonesia, 2008)
Human rights are universal, granted by God to all humans since their birth, and have been recognized by nations as written in the United Nations Charter and in other multilateral treaties. However, every state has its own characteristics and values in relation to social structures, religions, and geographical condition. Therefore, it is difficult to make the point of view of states about human rights similar, in the sense that human rights problem in a state is impossible to resolve in the same way as that in others. If the problems of human rights are resolved without considering social structures, the society will be detached from their own social structures, and will be difficult to develop values living in the society. Keywords: human rights, treaties, states, social structures